Analisis Hubungan Pelayanan Kefarmasian Terhadap Tingkat Kepuasan Pasien Program Rujuk Balik (PRB) BPJS Kesehatan Di Apotek Se-Kota Pekanbaru : Pendekatan Berbasis SERVQUAL - Afriani Hasan; Seftika Sari; Indriyati Hadi Ningrum (JURNAL FARMASI DAN MAKANAN, 2025)
The Chronic Disease Referral Program (Program Rujuk Balik/PRB) of the Indonesian National Health Insurance (BPJS Kesehatan) is designed to ensure continuity of care for patients with chronic diseases through affiliated community pharmacies. The success of this program is not only determined by drug availability but also by the implementation of pharmaceutical care standards that emphasize patient-centered services. This study aimed to analyze the characteristics of PRB patients, assess the implementation of pharmaceutical care standards in PRB pharmacies, evaluate patient satisfaction based on SERVQUAL dimensions, and examine the relationship between pharmaceutical service standards and patient satisfaction. This research employed a descriptive analytic design with a cross-sectional approach. A total of 140 PRB patients were recruited using proportional random sampling from affiliated pharmacies in Pekanbaru. Data were collected using patient characteristic questionnaires, observation checklists for pharmaceutical service standards, and the SERVQUAL instrument. Data analysis was performed using univariate, bivariate (Chi-Square test), and gap analysis. The results showed that most PRB patients were female (52.14%), middle-aged adults 41–60 years (62.86%), with secondary education (50.0%), occupations mainly entrepreneurs (38.57%), and monthly income above IDR 3,508,776 (57.9%). The overall implementation of pharmaceutical service standards was good (82.73%), with drug management (85%), clinical services (56.25%), human resources (90%), and facilities (100%). Patient satisfaction was categorized as very satisfied, with the highest score in empathy (95.93%) and the lowest in tangibles (90.35%). The Chi-Square test indicated a significant relationship between the implementation of pharmaceutical care standards and patient satisfaction (p = 0.002). In conclusion, PRB patient satisfaction in Pekanbaru was very high, yet clinical pharmacy services still require improvement. It is recommended that pharmacies strengthen counseling, therapy monitoring, and adverse drug reaction reporting to enhance both patient satisfaction and long-term clinical quality.